2024
DOI: 10.1001/jamapediatrics.2024.0492
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effectiveness of Newborn Screening for Spinal Muscular Atrophy

Oliver Schwartz,
Katharina Vill,
Michelle Pfaffenlehner
et al.

Abstract: ImportanceThere is increasing evidence that early diagnosis and treatment are key for outcomes in infants with spinal muscular atrophy (SMA), and newborn screening programs have been implemented to detect the disease before onset of symptoms. However, data from controlled studies that reliably confirm the benefits of newborn screening are lacking.ObjectiveTo compare data obtained on patients with SMA diagnosed through newborn screening and those diagnosed after clinical symptom onset.Design, Setting, and Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(53 reference statements)
0
0
0
Order By: Relevance
“…Finally, Cheng and Hsu commented on the proportion of symptomatic infants with 2 SMN2 copies within the NBS cohort at the initiation of treatment. Our data showed that 11 of 31 patients with 2 SMN2 copies were symptomatic at the start of treatment . This reflects the real-world experience with NBS for SMA and corresponds well to a systematic review by Aragon-Gawinska et al, which reported that approximately 50% of patients with 2 SMN2 copies identified by NBS were symptomatic at treatment initiation.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Finally, Cheng and Hsu commented on the proportion of symptomatic infants with 2 SMN2 copies within the NBS cohort at the initiation of treatment. Our data showed that 11 of 31 patients with 2 SMN2 copies were symptomatic at the start of treatment . This reflects the real-world experience with NBS for SMA and corresponds well to a systematic review by Aragon-Gawinska et al, which reported that approximately 50% of patients with 2 SMN2 copies identified by NBS were symptomatic at treatment initiation.…”
supporting
confidence: 89%
“…In Reply We appreciate the comments from Cheng and Hsu regarding our study on the clinical effectiveness of newborn screening (NBS) for spinal muscular atrophy (SMA). Their observations bring valuable perspectives that merit further discussion.…”
mentioning
confidence: 99%
“…To the Editor It was with great interest and appreciation that we read the article by Schwartz et al, which reported that functional outcomes and, thus, the response to treatment for spinal muscular atrophy (SMA) were significantly better in the newborn screening cohort than in the unscreened clinical symptom onset group. However, this study had some limitations.…”
mentioning
confidence: 99%
“…A nonrandomized cohort study in Australia analyzed, in addition to the above 2 methods, Hammersmith Infant Neurological Examination-2 (HINE-2) scores and compound muscle action potential data. These 2 assessments were included in the medical assessment section of the SMARTCARE protocol . However, the authors did not present the relevant data or analyses for these assessments.…”
mentioning
confidence: 99%
See 1 more Smart Citation